PEMANFAATAN KOPERASI SEKOLAH SEBAGAI SUMBER BELAJAR IPS DI SMP NEGERI KOTA BANJARBARU - Dwi Ika Mufitarini (JURNAL SOCIUS, 2014)
The existence of school cooperation is not running maximally. The assumption of this condition is that the system of management is poor and lack of participation or role of the students in the cooperative. This research is aimed at: 1) getting an overview of school cooperation at SMP Negeri Banjarbaru, 2) knowing whether schools can grow the participation of students in cooperative, 3) determining whether school cooperation at SMP Negeri Banjarbaru deserves to be as one of learning resources of IPS, and 4) determining how cooperative can function as a source of social science.This study used a qualitative approach. The results of this study indicate that : (1) The existence of school cooperative at SMP Negeri Banjarbaru is less noticed by the school as a source of social sciences, (2) The school cooperative at SMP Negeri Banjarbaru has not been able to grow participation of students in the cooperative, (3) School Cooperative at SMP Negeri Banjarbaru is not 100% suitable to be used as a source of social sciences, and (4) the school cooperative which can be used as a source of social sciences is the school cooperative which possesses a cooperative component or device.Keywords: Cooperative, Resources, Learning, Students